COMPONENTS, CRITERIA AND INDICATORS OF FUTURE PRIMARY SCHOOL TEACHERS' READINESS TO USE INNOVATIVE TECHNOLOGIES (Physical Culture and Sport: Scientific Perspective, 2022)
The training of a new generation of primary school teachers, who are able to depart from traditional forms and methods of working with students and at the same time perceive and extrapolate new pedagogical experience, new technologies, forms and methods of work in their professional activities, is aimed at realizing the need to create a positive educational environment by activating intellectual and sensory and emotional resources of each student. That is why there is a need to use appropriate pedagogical technologies in professional education. This, in turn, actualizes the need to include appropriate content in the subject-methodical training of future primary school teachers, requires rethinking and searching for new organizational forms and methods of training that would improve its quality and effectiveness, expand and deepen the content of professional training. This is due to the latest trends in the development of social, interstate, and cultural relations in the field of professional and pedagogical training of specialists and is the subject of special attention of the state, which is reflected in the main documents that determine the priorities of the educational policy of Ukraine: the laws of Ukraine "On Education", "On Higher Education" , "On the national informatization program", state programs "Information and communication technologies in education and science" for 2006-2010, Concept of implementation of state policy in the field of general secondary education reform "New Ukrainian school" for the period until 2029, Concept of media implementation of education in Ukraine (2010), Strategy for the development of the information society in Ukraine (2013), etc.
Keywords: professional readiness; pedagogical activity; components; cognitive; value-motivational; personal-activity